What is the comparative effectiveness of pharmacological versus lifestyle-based management strategies for menopausal symptoms in postmenopausal women? : A Systematic Review - Amanda Ezra Natasya Napitupulu; Jenary Immanuel Surbakti (International Medical Journal Corp. Ltd, 2026)
Introduction: Menopausal symptoms significantly impact quality of life for postmenopausal women. With growing concerns about hormone therapy safety and increasing interest in lifestyle approaches, evidence-based guidance on comparative effectiveness is urgently needed. This systematic review evaluates the comparative effectiveness of pharmacological versus lifestyle-based management strategies for menopausal symptoms. Methods: We systematically searched databases for randomized controlled trials, systematic reviews, meta-analyses, and prospective cohort studies published up to 2026 comparing pharmacological interventions (hormone therapy, SSRIs/SNRIs, gabapentin, clonidine) with lifestyle interventions (dietary modifications, exercise, cognitive behavioral therapy, acupuncture, herbal supplements) in postmenopausal women. Studies required ≥4 weeks duration and direct comparative design. Data extraction followed standardized protocols with quality assessment. Results: Eighty studies encompassing over 8,000 women were included. Hormone therapy demonstrated superior efficacy for vasomotor symptoms (70-90% reduction) compared to lifestyle interventions (1-3). SSRIs/SNRIs reduced symptoms by 40-60% (2,6). Among lifestyle interventions, acupuncture showed comparable effectiveness to pharmacological approaches (8,9,12), with additional cardiovascular benefits (12). Phytoestrogens demonstrated variable effectiveness (13,14), while exercise showed limited vasomotor benefits but improved quality of life (7,20). Combined approaches (pharmacological plus lifestyle) demonstrated superior outcomes (17,18). Safety profiles favored lifestyle interventions, with hormone therapy carrying highest serious adverse event risks (13,14). Discussion: Treatment selection should be individualized based on symptom severity, contraindications, and patient preferences. Hormone therapy remains most effective for severe symptoms in eligible women, while non-hormonal pharmacological and lifestyle options provide valuable alternatives. Acupuncture emerges as the most promising lifestyle intervention with comparable efficacy. Combined approaches may optimize outcomes. Conclusion: Pharmacological interventions, particularly hormone therapy, demonstrate superior efficacy for vasomotor symptoms, while lifestyle interventions offer favorable safety profiles and broader health benefits. An individualized, shared decision-making approach integrating both modalities is recommended.